Self-assembly material based on acridone, perovskite solar cell and preparation method

By using the π-electron conjugation on the benzene ring in the acridine self-assembly material to increase the carbonyl group, the problem of defects introduced by acridine self-assembly materials when modified at position 9 is solved, and more efficient perovskite solar cell performance is achieved.

CN119823182APending Publication Date: 2025-04-15ZHENGZHOU UNIV

Patent Information

Application Number
CN202510022122.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing acridinium self-assembly materials use steric hindrance effects to reduce exciton recombination by modifying different functional groups at position 9, but this is easy to introduce new defect sites, affecting the performance of perovskite solar cells.

Method used

Using acridine-based self-assembly materials, carbonyl groups are increased through the π-electron conjugation on the benzene ring, and the interaction with perovskite is enhanced, thereby passivating defects in the absorption layer and reducing non-radiative recombination of carriers.

Benefits of technology

It effectively improves the photoelectric conversion efficiency and filling factor of perovskite solar cells, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823182A_ABST
    Figure CN119823182A_ABST
Patent Text Reader

Abstract

The invention relates to an acridone-based self-assembly material, a perovskite solar cell and a preparation method, the self-assembly material has the following structure: # imgabs0 #, in which X1 and X2 are respectively and independently selected from hydrogen or halogen elements; l is alkylene or phenylene; a is a phosphate group; according to the acridone-based self-assembly material disclosed by the invention, the pi electron conjugation effect on a benzene ring is utilized, carbonyl groups are increased, the interaction with perovskite is enhanced, and the passivation effect on defects in a perovskite absorption layer can be improved, so that the non-radiative recombination of carriers is effectively reduced, the perovskite defects are fewer, the crystallinity is enhanced, the quality is higher, and the performance of the material is improved. The photoelectric conversion efficiency and filling factors of the cell are further improved, and the overall performance of the cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of perovskite solar cells, and in particular to an acridone-based self-assembly material and a preparation method and application thereof. Background Art

[0002] As an inexhaustible clean energy source, the progress of solar cell technology provides key support for the global energy transformation. Due to the low preparation cost of perovskite solar cells, the light-absorbing layer has many advantages such as adjustable band gap width and excellent photoelectric performance, the application range of perovskite solar cells has become very wide. In terms of energy conversion efficiency, the highest certified efficiency of single-junction organic-inorganic hybrid perovskite solar cells has reached 26.7%, becoming a research hotspot for the new generation of solar cells.

[0003] The self-assembled material (SAM) in perovskite is a class of molecules with strong hole-selective groups and anchoring groups. With its unique molecular structure, it can achieve the purpose of adjusting the crystal plane orientation, passivating defects, and improving the carrier transport performance in perovskite solar cells. Among them, the carbazole self-assembled system is easy to form dimers, and has poor wettability during the preparation process, which is not conducive to the preparation of high-efficiency perovskite solar cells; there are acridine self-assembled materials, such as a self-assembled hole-selective material based on acridine disclosed in CN 116178430 A, acridone compounds and their preparation methods and applications disclosed in CN 117924366 A, acridine derivative hole transport materials with phosphate anchoring disclosed in CN 118702727A, etc., because different functional groups (such as diphenyl, dimethyl, tetramethyl, etc.) are modified at the 9th position to reduce exciton recombination by using steric hindrance effect, but the steric hindrance effect is easy to introduce new defect sites. Summary of the invention

[0004] In view of this, the present disclosure proposes a self-assembly material based on acridone, a perovskite solar cell and a preparation method, which solves the problem that the existing acridone self-assembly material modifies different functional groups at the 9 position and uses the steric hindrance effect to reduce exciton recombination, but the steric hindrance effect easily introduces new defect sites.

[0005] To achieve the above-mentioned purpose of the invention, the inventive concept of the acridone-based self-assembly material is:

[0006] The acridone-based self-assembly material of the present invention utilizes the π electron conjugation effect on the benzene ring to increase the carbonyl group and enhance the interaction with the perovskite.

[0007] Based on the above inventive concept, in a first aspect, the present disclosure provides an acridone-based self-assembly material having a structure as shown below:

[0008]

[0009] Wherein, X1 and X2 are independently selected from hydrogen or halogen elements;

[0010] L is an alkylene group or a phenylene group;

[0011] A is a phosphate group.

[0012] In the present application and possible embodiments, L is (C2-C 18 )alkylene or (C2-C 18 )phenylene; the halogen element is selected from fluorine, chlorine, bromine and iodine.

[0013] In the present application and possible embodiments, L is (C2-C4) alkylene.

[0014] In a second aspect, the method for preparing the acridone-based self-assembly material according to the first aspect comprises the following steps:

[0015] Compound 1 is reacted with YLY to prepare compound 2;

[0016] Hydrolyzing the product of the mixed reaction of the compound 2 and triethyl phosphite to prepare the acridone-based self-assembly material 3;

[0017] The reaction equation is as follows:

[0018]

[0019]

[0020] wherein Y is selected from Br, I, and Cl;

[0021] X1 and X2 are independently selected from hydrogen or halogen elements, and the halogen elements are selected from fluorine, chlorine, bromine and iodine;

[0022] L is (C2-C 18 )alkylene or (C2-C 18 )phenylene.

[0023] In the present application and possible embodiments, the compound 1 is acridone, the YLY is dibromobutane, the compound 2 is 10-(4-bromobutyl)-2,7-dichloroacridin-9(10H)-one; the acridone-based self-assembly material 3 is 4-(2,7-dichloro-9-oxoacridin-10(9H)-yl)butyl)phosphonate;

[0024] Under alkaline conditions, a 1,4-dibromobutane solution of acridone and a 1,4-dibromobutane solution of tetrabutylammonium bromide are reacted at 40-90° C. for 8-20 hours and then quenched. The reaction product is extracted with dichloromethane, and then dried, the solvent is removed, and purified to obtain 10-(4-bromobutyl)-2,7-dichloroacridine-9(10H)-one;

[0025] A triethyl phosphite solution of 10-(4-bromobutyl)-2,7-dichloroacridin-9(10H)-one is reacted at 120-200° C. in a nitrogen atmosphere for 8-20 hours, and then the solvent is removed by rotary evaporation. Anhydrous 1,4-dioxane and trimethylsilyl bromide are added, and the mixture is stirred for 8-20 hours. The solvent is removed by rotary evaporation again, and methanol and deionized water are added. The mixture is stirred for 8-20 hours and then filtered. The mixture is precipitated in tetrahydrofuran and dichloromethane, and filtered to obtain 4-(2,7-dichloro-9-oxoacridin-10(9H)-yl)butyl)phosphonate.

[0026] In the present application and possible embodiments, the method of drying, removing solvent and purifying is:

[0027] The product was dried over anhydrous sodium sulfate, the solvent was removed by rotary evaporation, and the product was purified using petroleum ether / dichloromethane as eluent.

[0028] In a third aspect, the perovskite solar cell has a structure as follows:

[0029] Conductive glass layer, perovskite light absorbing layer and top electrode, or

[0030] Conductive glass layer, hole transport layer, perovskite light absorbing layer and top electrode, or

[0031] Conductive glass layer, perovskite light absorbing layer, electron transport layer and top electrode, or

[0032] Conductive glass layer, hole transport layer, perovskite light absorption layer, electron transport layer and top electrode;

[0033] The material of at least one functional layer includes the acridone-based self-assembly material described in any one of the first aspects.

[0034] In the present application and possible embodiments, an interface is set between the conductive glass layer and the hole transport layer, and / or between the hole transport layer and the perovskite light absorbing layer, and / or between the perovskite light absorbing layer and the electron transport layer, and / or between the electron transport layer and the top electrode, and the material of at least one of the interfaces includes the acridone-based self-assembled material described in any one of the first aspects.

[0035] In the present application and possible embodiments, the material of the conductive glass layer is selected from ITO, FTO, and AZO;

[0036] The material of the hole transport layer is selected from Spiro-OMeTAD, NiO X , PTAA or no hole transport layer;

[0037] The general structural formula of the material of the perovskite light absorbing layer is ABX3, wherein A is selected from Cs + 、MA + (CH3NH3 + ), FA + (CH(NH2)2 + );

[0038] The material of the electron transport layer is selected from PCBM, C 60 , C 70 SnO x 、TiO x or no electron transport layer;

[0039] The material of the top electrode is selected from gold, silver, aluminum, copper, conductive oxide, and carbon electrode.

[0040] In a fourth aspect, a method for preparing a perovskite solar cell according to the third aspect comprises:

[0041] A perovskite light absorbing layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a hole transport layer, a perovskite light absorbing layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a conductive glass layer, a perovskite light absorbing layer, an electron transport layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a hole transport layer, a perovskite light absorbing layer, an electron transport layer and a top electrode are sequentially prepared on one side of the conductive glass layer; the material of at least one functional layer includes the acridone-based self-assembled material described in any one of the first aspects.

[0042] The beneficial effects of the present invention are:

[0043] The acridone-based self-assembly material and the perovskite solar cell containing the material of the present invention utilize the π electron conjugation effect on the benzene ring to increase the carbonyl group and enhance the interaction with the perovskite, thereby improving the passivation effect on defects in the perovskite absorption layer, thereby effectively reducing the non-radiative recombination of carriers, and the perovskite has fewer defects, enhanced crystallinity, and higher quality, further improving the photoelectric conversion efficiency and fill factor of the battery, and improving the overall performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] The drawings herein are incorporated into the specification and constitute a part of the specification. These drawings illustrate embodiments consistent with the present disclosure and are used to illustrate the technical solutions of the present disclosure together with the specification.

[0045] Figure 1 is the nuclear magnetic spectrum of Ket-4ACPA of Example 1;

[0046] Figure 2 is the Fourier transform infrared spectrum of Ket-4ACPA and PbI2 of Example 1;

[0047] Figure 3 is a photoluminescence spectrum diagram of the interface between the hole transport layer and the perovskite light absorbing layer in Example 2 with or without Ket-4ACPA;

[0048] Figure 4 is the UV-visible light absorption spectrum of the interface between the hole transport layer and the perovskite light absorbing layer of Example 2 with or without Ket-4ACPA;

[0049] Figure 5 is an X-ray diffraction peak intensity diagram of the presence or absence of Ket-4ACPA at the interface between the hole transport layer and the perovskite light absorbing layer of Example 2;

[0050] Figure 6 is the photocurrent-voltage curve of the interface between the hole transport layer and the perovskite light absorbing layer in Example 2 with and without Ket-4ACPA;

[0051] Figure 7 is a photoluminescence spectrum of whether Ket-4ACPA of Example 3 acts on the perovskite light absorbing layer;

[0052] Figure 8 is the ultraviolet-visible light absorption spectrum of whether Ket-4ACPA of Example 3 acts on the perovskite light absorbing layer;

[0053] Fig. 9 is an X-ray diffraction peak intensity diagram showing whether the Ket-4ACPA of Example 3 acts on the perovskite light absorbing layer;

[0054] Fig.10 It is the photocurrent-voltage curve of whether Ket-4ACPA of Example 3 acts on the perovskite light absorbing layer. DETAILED DESCRIPTION

[0055] Various exemplary embodiments, features and aspects of the present disclosure will be described in detail below with reference to the accompanying drawings. The same reference numerals in the accompanying drawings represent elements with the same or similar functions. Although various aspects of the embodiments are shown in the accompanying drawings, the drawings are not necessarily drawn to scale unless otherwise specified.

[0056] In the present invention, "at least one" means more than one, such as one, two and more than two. "Multiple" or "several" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present invention, "several" means at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0057] If not specifically stated, all steps of the present invention may be performed sequentially or randomly. For example, the method includes steps 1 and 2, which means that the method may include steps 1 and 2 performed sequentially, or may include steps 2 and 2 performed sequentially. For example, the method may further include step 3, which means that step 3 may be added to the method in any order.

[0058] To solve the background technology problem, the present disclosure provides a self-assembly material based on acridone, having a structure as shown in the general formula:

[0059]

[0060] Wherein, X1 and X2 are independently selected from hydrogen (H) or halogen elements, and the halogen elements are selected from fluorine (F), chlorine (Cl), bromine (Br), and iodine (I);

[0061] L is (C2-C 18 )alkylene or (C2-C 18 )phenylene;

[0062] A is a phosphate group.

[0063] The following is a method for preparing acridone-based self-assembly material according to an embodiment of the present disclosure, and the steps are as follows:

[0064] Compound 1 is reacted with YLY to prepare compound 2;

[0065] Hydrolyzing the product of the mixed reaction of the compound 2 and triethyl phosphite to prepare the acridone-based self-assembly material 3;

[0066] The reaction equation is as follows:

[0067]

[0068]

[0069] wherein Y is selected from Br, I, and Cl;

[0070] X1 and X2 are independently selected from hydrogen (H) or a halogen element, wherein the halogen element is selected from fluorine (F), chlorine (Cl), bromine (Br), and iodine (I);

[0071] L is (C2-C 18 )alkylene or (C2-C 18 )phenylene.

[0072] The perovskite solar cell provided by the present disclosure has a structure as follows:

[0073] Conductive glass layer, perovskite light absorbing layer and top electrode, or conductive glass layer, hole transport layer, perovskite light absorbing layer and top electrode, or conductive glass layer, perovskite light absorbing layer, electron transport layer and top electrode, or conductive glass layer, hole transport layer, perovskite light absorbing layer, electron transport layer and top electrode; the material of at least one functional layer includes the acridone-based self-assembled material.

[0074] Furthermore, an interface is provided between the conductive glass layer and the hole transport layer, and / or between the hole transport layer and the perovskite light absorbing layer, and / or between the perovskite light absorbing layer and the electron transport layer, and / or between the electron transport layer and the top electrode, and the material of at least one of the interfaces includes the acridone-based self-assembly material.

[0075] The perovskite solar cell disclosed in the present invention, wherein the material of the conductive glass layer is selected from at least one of ITO, FTO and AZO; the material of the hole transport layer is selected from Spiro-OMeTAD, NiO X , PTAA or one or more or no hole transport layer; the general structural formula of the material of the perovskite light absorption layer is ABX3, wherein A is selected from Cs + 、MA + (CH3NH3 + ), FA + (CH(NH2)2 + ) The material of the hole transport layer is selected from Spiro-OMeTAD, NiO X , PTAA or one or more or no hole transport layer; the material of the electron transport layer is selected from PCBM, C 60 , C 70 SnO x 、TiO x One or more of or no electron transport layer; the material of the electrode layer is selected from one of gold, silver, aluminum, copper, conductive oxide and carbon electrode.

[0076] The method for preparing a perovskite solar cell according to an embodiment of the present disclosure comprises:

[0077] A perovskite light absorbing layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a hole transport layer, a perovskite light absorbing layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a conductive glass layer, a perovskite light absorbing layer, an electron transport layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a hole transport layer, a perovskite light absorbing layer, an electron transport layer and a top electrode are sequentially prepared on one side of the conductive glass layer; the material of at least one functional layer includes the acridone-based self-assembly material.

[0078] The following are preferred embodiments of the present disclosure.

[0079] Unless otherwise specified, the reagents, methods and equipment used in the examples are conventional reagents, methods and equipment in the art.

[0080] Embodiment 1

[0081] 1. Synthesis of acridone-based self-assembly material Ket-4ACPA. The specific synthesis steps are as follows:

[0082] 1. Synthesis of Compound 10-(4-bromobutyl)-2,7-dichloroacridin-9(10H)-one

[0083]

[0084] According to the above reaction equation, a 1,4-dibromobutane solution of acridone (0.1mM 10ml), a 1,4-dibromobutane solution of tetrabutylammonium bromide (1mM 10ml) and a 50% potassium hydroxide aqueous solution (10ml) were reacted at 65°C for 12h. The mixture was quenched, extracted with dichloromethane, dried over anhydrous sodium sulfate, and the solvent was removed by rotary evaporation. Finally, petroleum ether / dichloromethane was used as an eluent for purification to obtain compound 10-(4-bromobutyl)-2,7-dichloroacridin-9(10H)-one;

[0085] 2. Synthesis of compound Ket-4ACPA

[0086]

[0087] According to the above reaction equation, a triethyl phosphite solution (0.2mM20ml) of compound 2 (0.2mmol / l*20ml) was reacted at 160°C in a nitrogen atmosphere for 24h, and then the solvent was removed by rotary evaporation. Anhydrous 1,4-dioxane (5ml) and trimethylsilyl bromide (10ml) were added and stirred for 24h. The solvent was removed by rotary evaporation again, and methanol (5ml) and deionized water (10ml) were added. After stirring for 12h, the mixture was filtered, precipitated in tetrahydrofuran and dichloromethane, and filtered to obtain the final product Ket-4ACPA.

[0088] 2. Performance analysis and testing of compound Ket-4ACPA

[0089] 1. Nuclear magnetic resonance hydrogen spectrum analysis: The results are as follows Figure 1 As shown, by integrating hydrogen with different chemical shifts, it was found that there was a one-to-one correspondence with Ket-4ACPA and there were no impurity peaks, indicating that the synthesis quality of Ket-4ACPA was extremely high.

[0090] 2. Fourier infrared test: the results are as follows Figure 2 As shown, the characteristic absorption peak of carbonyl group is from 1588cm -1 Shift to 1592cm -1, proving that Ket-4ACPA can interact with PbI2 through the carbonyl group;

[0091] Embodiment 2

[0092] 1. Preparation of perovskite solar cells

[0093] The perovskite solar cell of Example 2 is composed of ITO glass, hole transport layer (nickel oxide), perovskite light absorption layer, electron transport layer (PCBM), interface modification layer (BCP) and silver electrode from bottom to top. It is prepared according to the following steps:

[0094] 1. The transparent conductive substrate was cleaned with glass cleaning agent, deionized water, industrial alcohol, anhydrous ethanol, and acetone in sequence, each ultrasonically treated for 20 minutes, and dried with nitrogen before use;

[0095] 2. Spin-coat nickel oxide dispersion and anneal at 150°C for 20 minutes;

[0096] 3. Weigh a certain amount of Ket-4ACPA and dissolve it in dimethyl sulfoxide (DMSO) to prepare a 1 mg / ml solution. Spin-coat the prepared Ket-4ACPA solution on nickel oxide at a speed of 3000 rpm for 30 seconds; anneal on a 100°C hot plate for 10 minutes and cool naturally to room temperature (this step is omitted for the control group);

[0097] 4. According to Cs 0.05 FA 0.85 MA 0.1 PbI3 was weighed in stoichiometric ratio, N,N-dimethylformamide (0.8 ml) and dimethyl sulfoxide (0.2 ml) were added, and stirred at 70°C until dissolved to obtain a perovskite precursor; the perovskite precursor was spin-coated at a speed of 3000 rpm for 30 seconds. 300 μL of chlorobenzene was taken as an anti-solvent and dripped in for 20 seconds, and annealed at 70°C for 60 minutes;

[0098] 5. Weigh a certain amount of PCBM and dissolve it in chlorobenzene to prepare a 25 mg / ml solution. Stir at 50°C until dissolved. Spin-coat the prepared PCBM solution on the perovskite light-absorbing layer at a speed of 2000 rpm for 30 seconds. Anneal on a 70°C heating plate for 5 minutes and cool naturally to room temperature.

[0099] 6. Dissolve BCP in isopropanol to prepare a saturated solution, and spin-coat the prepared BCP saturated solution on the PCBM electron transport layer at a speed of 5000 rpm for 30 seconds; anneal on a 70°C heating plate for 5 minutes, and cool naturally to room temperature;

[0100] 7. Pump the pressure of the thermal evaporation equipment to 1*10 -5 -5*10 -4Pa, turn on the evaporation power supply and thermally evaporate Ag onto the BCP interface modification layer at a deposition rate of 0.05-1 Å / s, a deposition thickness of 200 nm, and an area of ​​0.04 cm 2 ;

[0101] 2. Comparison of perovskite solar cells prepared based on acridone self-assembled material (Ket-4ACPA) according to the above steps and perovskite solar cells prepared in the control group:

[0102] 1. PL test: The results are as follows Figure 3 As shown, the Ket-4ACPA modified perovskite film exhibits a stronger PL peak intensity, indicating that the introduction of Ket-4ACPA effectively reduces the non-radiative recombination of carriers, indicating that the perovskite has fewer defects and higher quality.

[0103] 2. UV-visible light absorption test: The results are as follows Figure 4 As shown, the absorption of the Ket-4ACPA modified perovskite film is slightly enhanced at wavelengths below 800nm, indicating that the crystallinity of the film has been improved. The improvement of crystallinity can reduce the defects of perovskite to a certain extent.

[0104] 3. X-ray diffraction analysis: The results are as follows Figure 5 As shown in the figure, the typical peaks of perovskite appear at 13.92° and 28.15°, corresponding to the (001) and (002) crystal planes, respectively. The diffraction peak at 12.8° corresponds to PbI2. The ratio of PbI2 to the (001) crystal plane is significantly reduced, indicating that the crystallization of perovskite has been enhanced.

[0105] 4. JV curve test: The results are as follows Figure 6 As shown in Figure 2, the short-circuit current Jsc of the control group perovskite solar cell is 23.86 mA cm -2 , the open circuit voltage Voc is 0.91 V, the fill factor FF is 69.05%, and the photoelectric conversion efficiency PCE is 15.05%; the perovskite solar cell with Ket-4ACPA at the interface between the hole transport layer and the perovskite light absorption layer has a short circuit current Jsc of 24.14 mA cm -2 , the open circuit voltage Voc is 0.92V, the fill factor FF is 80.47%, and the photoelectric conversion efficiency PCE is 17.91%, which are much higher than those of the control group without adding the Ket-4ACPA interface layer.

[0106] Embodiment 3

[0107] 1. Preparation of perovskite solar cells

[0108] The perovskite solar cell of this embodiment 3 is composed of ITO glass, nickel oxide, perovskite light absorbing layer, PCBM, BCP and silver electrode from bottom to top; it is prepared according to the following steps:

[0109] 1. The transparent conductive substrate was cleaned with glass cleaning agent, deionized water, industrial alcohol, anhydrous ethanol, and acetone in sequence, each ultrasonically treated for 20 minutes, and dried with nitrogen before use;

[0110] 2. Spin-coat nickel oxide dispersion and anneal at 150°C for 20 minutes;

[0111] 4. According to Cs 0.05 FA 0.85 MA 0.1 PbI3 and Ket-4ACPA (1 mg) were weighed in a stoichiometric ratio (control group did not add Ket-4ACPA), N,N-dimethylformamide (0.8 ml) and dimethyl sulfoxide (0.2 ml) were added, and stirred at 70°C until dissolved to obtain a perovskite precursor; the perovskite precursor was spin-coated at a speed of 3000 rpm for 30 seconds. 300 μL of chlorobenzene was taken as an anti-solvent and dripped in for 20 seconds, and annealed at 70°C for 60 minutes;

[0112] 5. Weigh a certain amount of PCBM and dissolve it in chlorobenzene to prepare a 25 mg / ml solution. Stir at 50°C until dissolved. Spin-coat the prepared PCBM solution on the perovskite light-absorbing layer at a speed of 2000 rpm for 30 seconds. Anneal on a 70°C heating plate for 5 minutes and cool naturally to room temperature.

[0113] 6. Dissolve BCP in isopropanol to prepare a saturated solution, and spin-coat the prepared BCP saturated solution on the PCBM electron transport layer at a speed of 5000 rpm for 30 seconds; anneal on a 70°C heating plate for 5 minutes, and cool naturally to room temperature;

[0114] 7. Pump the pressure of the thermal evaporation equipment to 1*10 -5 -5*10 -4 After 100 Pa, turn on the evaporation power supply and thermally evaporate Ag or Al onto the BCP interface modification layer at a deposition rate of 0.05-1 Å / s, a deposition thickness of 200 nm, and an area of ​​0.04 cm 2 ;

[0115] 2. The following perovskite solar cells prepared based on acridone self-assembled material (Ket-4ACPA) according to the above steps are compared with the perovskite solar cells prepared in the control group:

[0116] 1. PL test: The results are as follows Figure 7 As shown, the Ket-4ACPA modified perovskite film exhibits a stronger PL peak intensity, indicating that the introduction of Ket-4ACPA effectively reduces the non-radiative recombination of carriers.

[0117] 2. UV-visible light absorption test: The results are as follows Figure 8 As shown, the absorption of the Ket-4ACPA modified perovskite film is slightly enhanced at wavelengths below 800 nm, indicating that the crystallinity of the film is improved.

[0118] 3. X-ray diffraction analysis: The results are as follows Fig. 9 As shown, the ratio of PbI2 to (001) crystal plane is significantly reduced, indicating that the crystallization of perovskite is enhanced.

[0119] 4. JV curve test: The results are as follows Fig.10 As shown in Figure 2, the short-circuit current Jsc of the control group perovskite solar cell is 23.86 mA cm -2 , the open circuit voltage Voc is 0.91V, the fill factor FF is 69.05%, and the photoelectric conversion efficiency PCE is 15.05%; the short circuit current Jsc of the perovskite solar cell with Ket-4ACPA acting on the perovskite light absorption layer is 25.82mA cm -2 The open circuit voltage Voc is 1.03V, the fill factor FF is 80.14%, and the photoelectric conversion efficiency PCE is only 21.30%, which is much higher than that of the device without adding Ket-4ACPA.

[0120] It can be understood that the above-mentioned various method embodiments mentioned in the present disclosure can be combined with each other to form a combined embodiment without violating the logic of the principle. Due to space limitations, the present disclosure will not go into details. The various embodiments of the present disclosure have been described above. The above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Without departing from the scope and spirit of the described embodiments, many modifications and changes are obvious to those of ordinary skill in the art. The choice of terms used in this article is intended to best explain the principles of the embodiments, practical applications, or technical improvements to the technologies in the market, or to enable other ordinary technicians in the technical field to understand the embodiments disclosed herein.

Claims

1. A self-assembly material based on acridone, characterized in that: It has the following structure: Wherein, X1 and X2 are independently selected from hydrogen or halogen elements; L is an alkylene group or a phenylene group; A is a phosphate group.

2. The acridone-based self-assembly material according to claim 1, characterized in that: The L is (C2-C 18 )alkylene or (C2-C 18 )phenylene; the halogen element is selected from fluorine, chlorine, bromine and iodine.

3. The acridone-based self-assembly material according to claim 2, characterized in that: The L is a (C2-C4) alkylene group.

4. The method for preparing the acridone-based self-assembly material according to claim 1, characterized in that: The steps of the preparation method are as follows: Compound 1 is reacted with YLY to prepare compound 2; Hydrolyzing the product of the mixed reaction of the compound 2 and triethyl phosphite to prepare the acridone-based self-assembly material 3; The reaction equation is as follows: wherein Y is selected from Br, I, and Cl; X1 and X2 are independently selected from hydrogen or halogen elements, and the halogen elements are selected from fluorine, chlorine, bromine and iodine; L is (C2-C 18 )alkylene or (C2-C 18 )phenylene.

5. The method for preparing the acridone-based self-assembly material according to claim 4, characterized in that: The compound 1 is acridone, the YLY is dibromobutane, the compound 2 is 10-(4-bromobutyl)-2,7-dichloroacridin-9(10H)-one; the acridone-based self-assembly material 3 is 4-(2,7-dichloro-9-oxoacridin-10(9H)-yl)butyl)phosphonate; Under alkaline conditions, a 1,4-dibromobutane solution of acridone and a 1,4-dibromobutane solution of tetrabutylammonium bromide are reacted at 40-90° C. for 8-20 hours and then quenched. The reaction product is extracted with dichloromethane, and then dried, the solvent is removed, and purified to obtain 10-(4-bromobutyl)-2,7-dichloroacridine-9(10H)-one; A triethyl phosphite solution of 10-(4-bromobutyl)-2,7-dichloroacridin-9(10H)-one is reacted at 120-200° C. in a nitrogen atmosphere for 8-20 hours, and then the solvent is removed by rotary evaporation. Anhydrous 1,4-dioxane and trimethylsilyl bromide are added, and the mixture is stirred for 8-20 hours. The solvent is removed by rotary evaporation again, and methanol and deionized water are added. The mixture is stirred for 8-20 hours and then filtered. The mixture is precipitated in tetrahydrofuran and dichloromethane, and filtered to obtain 4-(2,7-dichloro-9-oxoacridin-10(9H)-yl)butyl)phosphonate.

6. The method for preparing the acridone-based self-assembly material according to claim 5, characterized in that: The method of drying, removing solvent and purifying is as follows: The product was dried over anhydrous sodium sulfate, the solvent was removed by rotary evaporation, and the product was purified using petroleum ether / dichloromethane as eluent.

7. A perovskite solar cell, characterized in that: Its structure is: Conductive glass layer, perovskite light absorbing layer and top electrode, or Conductive glass layer, hole transport layer, perovskite light absorbing layer and top electrode, or Conductive glass layer, perovskite light absorbing layer, electron transport layer and top electrode, or Conductive glass layer, hole transport layer, perovskite light absorption layer, electron transport layer and top electrode; The material of at least one functional layer comprises the acridone-based self-assembly material according to any one of claims 1 to 3.

8. The perovskite solar cell according to claim 7, characterized in that: An interface is set between the conductive glass layer and the hole transport layer, and / or between the hole transport layer and the perovskite light absorbing layer, and / or between the perovskite light absorbing layer and the electron transport layer, and / or between the electron transport layer and the top electrode, and the material of at least one of the interfaces includes the acridone-based self-assembled material according to any one of claims 1 to 3.

9. The perovskite solar cell according to claim 7 or 8, characterized in that: The material of the conductive glass layer is selected from ITO, FTO, and AZO; The material of the hole transport layer is selected from Spiro-OMeTAD, NiO X , PTAA or no hole transport layer; The general structural formula of the material of the perovskite light absorbing layer is ABX3, wherein A is selected from Cs + 、MA + (CH3NH3 + ), FA + (CH(NH2)2 + ); The material of the electron transport layer is selected from PCBM, C 60 , C 70 SnO x 、TiO x or no electron transport layer; The material of the top electrode is selected from gold, silver, aluminum, copper, conductive oxide, and carbon electrode.

10. A method for preparing the perovskite solar cell according to claim 9, characterized in that: include: A perovskite light absorbing layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a hole transport layer, a perovskite light absorbing layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a conductive glass layer, a perovskite light absorbing layer, an electron transport layer and a top electrode are sequentially prepared on one side of the conductive glass layer, or a hole transport layer, a perovskite light absorbing layer, an electron transport layer and a top electrode are sequentially prepared on one side of the conductive glass layer; the material of at least one functional layer includes the acridone-based self-assembled material according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Self-assembly hole selection material based on acridine and preparation method and application thereof

    CN116178430A

  • Self-assembly molecular material, preparation method and application thereof, solar cell and preparation method thereof

    CN118955561A

  • Novel compound, and light emitting device comprising same

    WO2014003405A1

Cited By

  • Acridone derivative, hole transport layer and perovskite solar cell

    CN121949396A